Studi Pembuatan Teh Daun Tanaman Kakao (Theobroma cacao L) sebagai Minuman Penyegar - Supriyanto Supriyanto; Purnama Darmadji; Iik Susanti (agriTECH, 2014)
In the cultivation of cocoa plant, leaf trimming is done at any given time interval. Leaves pruned are not used optimally and are normally wasted during frequent pruning, whereas cocoa leaves contain polyphenols and has antioxidant activity equivalent and similar to green tea, even greater than in green tea. This study was aimed to assess the possibility of utilization of cocoa trees pruned leaves as a tea for a refreshing beverage that is processed in accordance with the principles of green tea processing. Young cocoa leaves that is the apex plus 3 leaves below it, and the old leaves that is 5 th leaf to the 8 th leaf, are withered at a temperature of 90-100 oC RH <70% for 5, 10 and 15 minutes. The leaves wilt then milled/rolled at ambient temperature, dried at 90-100 oC for 4 hours to dry cocoa leaves until  the moisture content reaches of 3-5%. Observation and analysis were done, including the moisture content, color, total polyphenol content, and  antioxidant activity on powdered cocoa leaf tea and sensory test on a refreshing beverage. The results showed that refreshing beverages from cocoa leaf tea boiled water can be accepted by the panelists, and panelists most preferred the refreshing beverage made from young cocoa leaves withered for 10 minutes. The beverage  is very brown color, slightly smelling leaves, slightly bitter and slightly astringent. Powdered cocoa leaf tea contain a total polyphenols between 0.42 to 0.74 mg/100 g, have antioxidant activity between 20.31 to 36.86%, not much different from the antioxidant activity of green tea commercial, amounting to 16% even slightly larger.ABSTRAKPada budidaya tanaman kakao perlu dilakukan pemangkasan daun pada setiap waktu tertentu. Daun hasil pangkasan belum dimanfaatkan secara optimal, padahal daun kakao mengandung polifenol dan mempunyai aktivitas antioksidan setara dan serupa dengan teh hijau, bahkan lebih besar dari pada teh hijau. Penelitian ini bertujuan untuk mengkaji kemungkinan pemanfaatan daun tanaman kakao hasil pangkasan sebagai teh untuk minuman penyegar yang dipersiapkan seperti pada pengolahan teh hijau. Daun kakao muda yaitu pucuk ditambah 3 daun dibawahnya (1-4) dan daun tua yaitu daun nomer 5 dan 3 daun dibawahnya dilayukan pada suhu 90-100 C RH <70% selama 5, 10 dan 15 menit. Daun layu kemudian digiling/digulung pada suhu ruang, dikeringkan pada suhu 90-100 oC selama 4 jam hingga dihasilkan daun kakao kering berkadar air 3-5%. Dilakukan pengamatan dan analisis meliputi kadar air, warna, kadar total polifenol, aktivitas antioksidan dan uji sensoris pada air rebusan teh daun kakao sebagai minuman penyegar. Hasil penelitian menunjukkan bahwa minuman penyegar hasil rebusan teh daun kakao dapat diterima oleh panelis, dan  yang paling disukai adalah air rebusan teh yang dibuat dari daun kakao muda dilayukan 10 menit. Air rebusan tersebut  warnanya sangat coklat, sedikit berbau daun, agak pahit dan sedikit sepat. Bubuk teh daun kakao mengandung total polifenol antara 0,42-0,74 mg/100 g, mempunyai aktivitas antioksidan antara 20,31 – 36,86%.